Analisis Drug Related Problems (DRPs) Pasien Diabetes Melitus Tipe 2 - Handayani, Dian; Versita, Riana; Putri, Denaranny Gita; Hayati, Risda; Lestari, Feny (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2023)
Diabetes mellitus (DM) is a global health problem, DM patients are increasing every year. The presence of comorbidities and various risk factors for patients with type 2 diabetes mellitus causes patients to often consume more than two kinds of drugs and can risk ineffective treatment and allow drug related problems (DRPs) to occur. The purpose of study was to determine the description of drug related problems (DRPs) in type 2 diabetes mellitus patients. His research is an analytic observational study with a cross sectional design. Prospective data collection. The analysis was carried out using univariate and bivariate analysis. types of drug related problems (DRPs) that occur include that 7 patients are not treated (20%), inappropriate drug selection 17 patients (48,6%), 1 patient over dose (2,8%), and drug interactions 3 patients (8,6%).